Trends in mortality statistics in England and Wales with particular reference to AIDS from 1984 to April 1987. Issue 6632 (7th May 1988) - McCormick, Anna
Abstract : Death certification should be able to provide accurate data on the number of deaths due to AIDS as a basis for predicting future deaths from the syndrome. Trends in deaths from other causes may identify conditions that have not been recognised to be associated with HIV infection. Mortality statistics with reference to AIDS in England and Wales were completed from death certificates. Increases in deaths from selected causes likely to be associated with AIDS or HIV infection suggested that in some patients with HIV infection, AIDS was not stated on the death certificate or subsequently notified by the doctor who signed the certificate. From calculations of excess deaths between the beginning of 1985 and the end of April 1987, compared with 1984 at least 495 deaths possibly associated with HIV infection were estimated to have occurred among men aged 15-54 during that period. In 261 AIDS or HIV infection was stated on the original or amended death entry as the cause of death, and of these 198 were included in the estimated number of excess deaths. Accurate notification of the underlying cause of death and associated diseases is required for the precise monitoring of trends in mortality from AIDS and possible identification of unrecognised conditions associated with HIV infection.